El pasado presente: reflexiones sobre el actual contexto historiográfico / The Past Present: Reflections on the Current Historiographic Context - Prades Plaza, Sara (Historiografías, 2017)
En este artículo se reflexiona sobre la actual coyuntura historiográfica para concluir que existe hoy una crisis de paradigmas. Factores tales como cambio en los regímenes de historicidad, los actuales usos públicos de la Historia, el triunfo de la Historia reciente, la entrada de otros profesionales no historiadores en el campo de los estudios históricos, la centralidad del individuo y la posibilidad de dar voz a los vencidos son los principales rasgos de una nueva coyuntura historiográfica del siglo XXI, que viene como de la crisis de la modernidad. Palabras clave Usos públicos de la Historia, historiador, historiografía, memoria, Historia reciente. Abstract This article is a reflection on the present historiographical situation which concludes that we are witness of a crisis of paradigms today. Factors such as a change in the regimes of historicity, the importance of public uses of history, the triumph of recent history, the contribution of other professionals, apart from historians, to the field of historical studies, the centrality of the individual, and the possibility of giving voice to the losers are all the principal features of a new 21th century historiographic panorama which stems from the current crisis of modernity. Key Words Public uses of history, historian, historiography, memory, recent history